Immunological function of HLA-C antigens in HLA-Cw3 transgenic mice. - Dill, O (1988)
The human major histocompatibility complex encodes three classical class I antigens, HLA-A, -B, and -C. Of these HLA-A and -B act as strong transplantation antigens and as restriction molecules for recognition of foreign antigen by cytotoxic T lymphocytes. In contrast, little is known about HLA-C and it is not clear whether HLA-C has the same functional properties as HLA-A and -B. Transgenic C57BL/6 mice expressing the HLA-Cw3 gene were established. Functional studies demonstrated that transgenic skin was rapidly rejected by normal C57BL/6 mice and that cytotoxic T lymphocytes generated by immunization of the Cw3 transgenic mice with influenza and Sendai virus were restricted by the Cw3 molecule. These data suggest that HLA-Cw3 has immunological functions comparable to those of HLA-A and -B.